Swim performance following creatine supplementation in division III athletes - Selsby, J. T.; Beckett, K. D.; Kern, M.; Devor, S. T. (The Journal of Strength and Conditioning Research, 2003)
Creatine (Cr) supplementation has yielded inconsistent results when applied to competitive swimming. To further define the role of Cr, we tested the hypothesis that a Cr supplementation group of Division III swimmers would demonstrate enhanced performance when compared with placebo. In order to test this hypothesis, 8 male and 7 female collegiate Division III swimmers were assigned in a random, double-blind manner into either a Cr supplementation group (0.3 g Cr·kg 1 body mass) or a placebo group. Loading was maintained for 5 days followed by a 9-day period where Cr-supplemented subjects consumed 2.25 g Cr regardless of body weight. A 50- and 100-yd sprint was performed prior to and following the supplementation regimens. The Cr supplementation group decreased their finish times in both the 50- and 100-yd sprints. Support of the hypothesis suggests that Cr supplementation for swimming events is effective for singular effort sprints of 50 and 100 yd in Division III athletes.